Konsep Pelestarian Lingkungan Dalam Upacara Tumpek Wariga Sebagai Media Pendidikan Bagi Masyarakat Hindu Bali - I Ketut Sudarsana (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2017)
Environment is a place close to the existence of human life, but the environment also has significance for humans. With the physical environment man can use it to meet his material needs, with the human biological environment to meet his physical needs, and with his social environment man can meet his spiritual needs. This research has found that Tumpek Wariga as the local wisdom of the Balinese Hindu community is not an offering for plants, but a ceremony made, presented to the Lord. This means the ceremony is to express God's gratitude. The implementation of the ceremony Tumpek Wariga provides education to all Hindus of the importance of conservation, especially the preservation of plants.